2010
DOI: 10.1002/pd.2434
|View full text |Cite
|
Sign up to set email alerts
|

Trends in prenatal screening and diagnostic testing among women referred for advanced maternal age

Abstract: Improved prenatal screening tests and increased availability of screening for AMA patients has led to a steady decline in uptake of invasive testing from 2001 through 2007. This trend reversed from 2007 through 2008. Possible reasons for this reversal are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 18 publications
3
47
0
Order By: Relevance
“…A recent study by Nakata et al evaluated 163 756 patients referred to Genzyme Genetics for genetic counseling because of advanced maternal age, from 2001 to 2008. 6 During this period, firsttrimester screening increased from 45 to 85%; however, the authors found a decrease in amniocentesis from 56 to 31% and in CVS from 36 to 14% over the same period. The effect of large systemwide prenatal screening programs was also described by Ekelund et al 7 In their study detailing the effect of the Danish Prenatal Screening Program, the authors described a decrease in the number of prenatal diagnostic procedures performed (4202 to 1208 amniocentesis and 3322 to 2302 CVS procedures) from 2000 to 2006 while the uptake in prenatal screening reached 84% over the same period.…”
Section: Discussionmentioning
confidence: 80%
“…A recent study by Nakata et al evaluated 163 756 patients referred to Genzyme Genetics for genetic counseling because of advanced maternal age, from 2001 to 2008. 6 During this period, firsttrimester screening increased from 45 to 85%; however, the authors found a decrease in amniocentesis from 56 to 31% and in CVS from 36 to 14% over the same period. The effect of large systemwide prenatal screening programs was also described by Ekelund et al 7 In their study detailing the effect of the Danish Prenatal Screening Program, the authors described a decrease in the number of prenatal diagnostic procedures performed (4202 to 1208 amniocentesis and 3322 to 2302 CVS procedures) from 2000 to 2006 while the uptake in prenatal screening reached 84% over the same period.…”
Section: Discussionmentioning
confidence: 80%
“…3 In some clinical settings, amniocentesis or CVS for aneuploidy has been offered to all pregnant women of advanced maternal age. [4][5][6] In other circumstances or countries, discussion of invasive testing may be prompted by a high-risk screening result. 7 However, the opportunity to use non-invasive techniques for some conditions is now feasible 8 and these are increasingly available to women in some countries.…”
mentioning
confidence: 99%
“…Despite these concerns, research has demonstrated that more than half of AMA women choose to undergo IDTs (Nakata et al, 2010). As uptake of amniocentesis seems to be higher in this group, in comparison with women with a positive screening test (Hoskovec et al, 2008), our study specifically considers the experience of women of AMA as the sole indication for genetic counseling.…”
Section: Advanced Maternal Age and Prenatal Testingmentioning
confidence: 99%
“…Considering these implications, the study of the decision-making process regarding IDTs (i. e., how couples make a decision whether or not to undergo these tests) appears to be extremely relevant. Our study will specifically focus amniocentesis, as this is the most frequently chosen test (Nakata et al, 2010).…”
Section: Advanced Maternal Age and Prenatal Testingmentioning
confidence: 99%
See 1 more Smart Citation